Analysis and Design of Thin Film Coatings and Deep-Etched Waveguide Gratings for Integrated Photonic Devices - Zhou, Guirong (My University, 2002)
This thesis aims at investigating the feasibility of realizing antireflection (AR) and high-reflection (HR) to the semiconductor waveguide end facet using monolithically integratable deep-etching technology to replace the conventional thin film dielectric coating counterpart. Conventional AR coating and HR coatings are the building blocks of semiconductor optical amplifier and semiconductor lasers. In this thesis, the AR coating and HR coating are first studied systematically and comprehensively using two computational electromagnetics approaches: plane wave transmission matrix method (TMM) and finite difference time domain (FDTD) method. The comparison of the results from the two approaches are made and discussed. A few concepts are clarified based on the different treatment between the AR coatings for bulk optics and those for semiconductor waveguide laser structure. The second part uses the same two numerical tools and more importantly, the knowledge gained from the first part to analyze and design deep-etched waveguide gratings for the advantage of ease of monolithic integration. A variational correction to the TMM is provided in order to consider effect of the finite etching depth also in the plane wave model. Specially, a new idea of achieving AR using deep-etched waveguide gratings is proposed and analyzed comprehensively. A preliminary design is obtained by TMM optimization and FDTD verifications, which provides a minimum power reflectivity in the order of 10-5 and a bandwidth of 45nm for the power reflectivity less than 10-3. In order to eliminate the nonphysical reflections from the boundary, the perfectly matched layer (PML) absorbing condition is employed and pre-tested for antireflection analysis. The effects of etching depth and number of etching grooves are specifically analyzed for the performance of proposed structures. Numerical results obtained by FDTD method indicate a promising potential for this alternative technologies.
Deep-Etched Waveguide Gratings for Photonic Devices
Keywords: thin film coatings; deep-etched waveguide grating; integrated photonic device